Headache at the emergency room: Etiologies, diagnostic usefulness of the ICHD 3 criteria, red and green flags (2019)
Introduction Non-traumatic headaches account for 0.5 to 4.5% at the emergency department (ED). Although primary headaches represent the most common causes, the likelihood of ominous etiology has to be considered by clinicians in order to avoid diagnostic and therapeutic pitfalls. Due to the absence of biological or imaging findings to diagnose primary headaches we hypothesize ICHD 3(International Headache criteria 3) criteria as a useful tool at the moment to identify and to establish a difference between those patients who are undergoing primary headaches and those who will need advanced diagnostic strategies. Objectives To determine the usefulness of ICHD 3 criteria to differentiate primary from non-primary headaches at the emergency department (ED). Methods During five weeks all the patients complaining of headache attended at the triage unit at the ED were interviewed, examined and classified as having primary or non-primary headaches by means of ICHD 3 criteria. Those patients with primary headaches were treated according to standard of care protocols and followed up by means of phone call communication after 48 hours to assure satisfactory outcome. Those patients classified as having non-primary headaches (secondary headaches and neuralgias) were admitted for additional diagnostic and therapeutic interventions. Between both groups we compared the prevalence of fulfilled criteria for primary headaches and the proportion of traditional red flags such as age, sleep headache onset, associated symptoms, abnormal neurological exam, sudden onset, and nonresponse to analgesics in addition to previous consultation before this evaluation. Results Headache was responsible for 244 (2.3%) out of 10450 admissions at the ED, 77.8% were females. Primary, non-primary (secondary plus neuralgias) and unclassified headaches were 59.4%, 32% and 8.6% respectively. Migraine and cervical myofascial pain were the most frequent etiologies for primary and non-primary causes respectively. Factors associated to non-primary etiologies were immunosuppression (OR: 2.7 IC 95% 2.3–3.3) and age older than 50 (OR: 2.7 IC 95% 2.01–3.62). Abnormal neurological exam, sudden and sleep headache onset were not statistically significant. Factors found to be associated with primary headaches were: fulfilling ICHD 3 criteria (OR: 18.7, IC95% 7.1–48.6), history of migraine (OR: 2.9 IC 95% 2.1–3.9), and history of similar episodes (OR: 2.7 IC 95% 2.3–3.3). Conclusion This data suggests that fulfilling ICHD 3 criteria could be useful to differentiate primary from non-primary headaches. This observation is also valid for immunosuppression, age older than 50, history of migraine and history of similar episodes. © 2019 Munoz-Ceron et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.